Dosage effects of Waxy gene on the structures and properties of corn starch. (20th September 2016) - Yangcheng, Hanyu; Blanco, Michael; Gardner, Candice; Li, Xuehong; Jane, Jay-lin
Highlights: The Waxy gene had dosage effects on the contents and structures of amylose and amylopectin. Percentage of extra-long branch-chains positively correlated with the Waxy -gene dosage. Percentage of short branch-chains negatively correlated with the Waxy -gene dosage. Gelatinization temperature-range negatively correlated with the Waxy -gene dosage. Abstract: The objective of this study was to understand dosage effects of the Waxy gene on the structures of amylose and amylopectin and on the properties of corn starch. Reciprocal crossing of isogenic normal and waxy corn lines was conducted to develop hybrids with different dosages (0, 1, 2, 3) of Waxy gene in the endosperm. The amylose content of starch and proportions of branch chains of DP 17–30 and extra-long branch chains (DP > 100) of amylopectin were positively correlated with the Waxy -gene dosage. Proportions of short (DP < 17) and long branch-chains (DP 30–80), however, were negatively correlated with the Waxy -gene dosage. The gelatinization conclusion-temperature and temperature-range of the starch were negatively correlated with the Waxy -gene dosage, indicating that amylose facilitated dissociation of the surrounding crystalline regions. These results helped us understand the function of granule-bound starch synthase I in the biosynthesis of amylose and amylopectin and impacts of Waxy -gene dosages on the properties of corn starch.